2018
DOI: 10.3892/mmr.2018.9761
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR‑542‑3p in osteosarcoma with miRNA microarray data, and its potential signaling pathways

Abstract: Osteosarcoma (OS) is the most common pediatric primary bone tumor, with high malignancy rates and a poor prognosis following metastasis. At present, the role of microRNA (miR)-542-3p in OS remains to be elucidated. The purpose of the present study was to investigate the expression level of miR-542-3p in OS, and its potential molecular mechanisms, via a bioinformatics analysis. First, the expression of miR-542-3p in OS based on the continuous variables of the Gene Expression Omnibus database and PubMed was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…Our bioinformatics analyses of key target genes revealed that alanine, aspartate and glutamate metabolism and GABAergic synapse were significant KEGG pathways and in total, eight significantly enriched GO terms were identified, which might indicate the potential molecular mechanisms of miR-542-3p upon MTX therapy. Inconsistent with our findings, previous studies have shown that miR-542-3p was significantly increased in osteosarcoma tissue, and its bioinformatics analyses revealed that the sphingolipid signalling pathway ( p = 3.91 × 10 −5 ) and bone development were the most highlighted pathway and GO term, respectively [ 30 ]. These investigations demonstrated that the target genes and biological functions of miR-542-3p may vary with different pathological conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our bioinformatics analyses of key target genes revealed that alanine, aspartate and glutamate metabolism and GABAergic synapse were significant KEGG pathways and in total, eight significantly enriched GO terms were identified, which might indicate the potential molecular mechanisms of miR-542-3p upon MTX therapy. Inconsistent with our findings, previous studies have shown that miR-542-3p was significantly increased in osteosarcoma tissue, and its bioinformatics analyses revealed that the sphingolipid signalling pathway ( p = 3.91 × 10 −5 ) and bone development were the most highlighted pathway and GO term, respectively [ 30 ]. These investigations demonstrated that the target genes and biological functions of miR-542-3p may vary with different pathological conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Previous evidence showed that Wnt signalling and TGF-β signalling are the highlighted signalling pathways that can be affected by miR-542-3p [ 30 , 31 ]. Consistently, sFPR-1 and Smurf2, two direct targets identified in the current study, are known as antagonists for Wnt signalling and TGF-β signalling, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs) in CF. Although CF is monogenic, the phenotypes of patients with CF are heterogeneous, which may be attributed to multiple regulators that contribute to CF pathogenesis (53) (53,(57)(58)(59). The inhibition of miR-145 through peptide nucleic acids was reported to promote the expression of CFTR, as miR-145 binds to the 3'-untranslated region (3'UTR) of the CFTR gene (57).…”
Section: Molecular Regulators In Cfmentioning
confidence: 99%